2018
DOI: 10.3892/ijmm.2018.3746
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑26a protects vascular smooth muscle cells against H2O2‑induced injury through activation of the PTEN/AKT/mTOR pathway

Abstract: Abdominal aortic aneurysm (AAA) is a common disease, which is characterized by the apoptosis of vascular smooth muscle cells (VSMCs). In previous years, microRNAs (miRNAs) have been associated with AAA and functionally implicated in the pathogenesis of this disease. However, the role of miRNAs in the apoptosis of VSMCs remains to be fully elucidated. The present study aimed to elucidate the role and mechanism of miRNAs in protecting against hydrogen peroxide (H2O2)-induced apoptosis in VSMCs. The expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 47 publications
(48 reference statements)
0
29
0
Order By: Relevance
“…The Akt inhibitor API‐2 can reverse the anti‐apoptotic effect of miR‐26a on VSMCs, thereby having a protective effect on VSMCs. Together, these results indicated that miR‐26a protected VSMCs from H 2 O 2 ‐induced damage by activating the PTEN/AKT/mTOR pathway (Peng et al, ). SMAD1 and SMAD4 are two TGF‐β and BMP‐associated differentiation‐promoting factors, and overexpression of miR‐26a inhibited VSMCs differentiation and helped maintain cell balance in both synthetic and contractile states.…”
Section: Vsmc Proliferation Migration and Apoptosismentioning
confidence: 81%
See 1 more Smart Citation
“…The Akt inhibitor API‐2 can reverse the anti‐apoptotic effect of miR‐26a on VSMCs, thereby having a protective effect on VSMCs. Together, these results indicated that miR‐26a protected VSMCs from H 2 O 2 ‐induced damage by activating the PTEN/AKT/mTOR pathway (Peng et al, ). SMAD1 and SMAD4 are two TGF‐β and BMP‐associated differentiation‐promoting factors, and overexpression of miR‐26a inhibited VSMCs differentiation and helped maintain cell balance in both synthetic and contractile states.…”
Section: Vsmc Proliferation Migration and Apoptosismentioning
confidence: 81%
“…Thus, it was confirmed that miR‐26a had a regulatory effect on PDGF‐BB‐mediated Smad1 expression in VSMCs. Peng et al () show that miR‐26a expression was down‐regulated in VSMCs after H 2 O 2 stimulation. However, up‐regulation of miR‐26a attenuated H 2 O 2 ‐induced cell damage by enhancing cell viability, and inhibiting caspase‐3 activity, apoptosis, and reactive oxygen species production.…”
Section: Vsmc Proliferation Migration and Apoptosismentioning
confidence: 99%
“…Kang et al 16 and Peng et al 17 demonstrated that miR‐26a‐5p has protective effects against H 2 O 2 ‐induced cytotoxicity and apoptosis in vascular smooth muscle and RGC‐5 cells through downregulation of PTEN. Moreover, the anti‐apoptotic and pro‐survival potential of miR‐26a‐5p by targeting PTEN gene has been reported in sperm cells 18 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR‐26a‐5p is a small non‐coding RNA that has activation effect on cell proliferation and apoptosis with activation of PI3K/AKT signaling pathway via targeting phosphatase and tensin homolog gene (PTEN) 15 . It has been shown that miR‐26a‐5p protects vascular smooth muscle and RGC‐5 cells against H 2 O 2 ‐induced cytotoxicity and apoptosis through downregulation of PTEN 16,17 . Ma et al 18 reported the association of sperm quality and motility with miR‐26a‐5p by targeting PTEN 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The samples were assessed using the miRCURY LNA™ Array v. 18.0 (Agilent). The procedure and imaging processes were as described previously (Peng et al 2018).…”
Section: Mirna Microarraymentioning
confidence: 99%